Improving energy estimation in VSA processes through integration of vacuum pump characteristics: A carbon capture case study - Gholami, Mohsen; Schoukens, Matthias; Van Assche, Tom R.C.; Denayer, Joeri F.M. (Separation and purification technology, 2024)
[Display omitted] •The performance curve of the vacuum pump was integrated to the VSA simulation code.•Vacuum pump's nominal power was used to estimate energy consumption.•An efficiency factor for electrical to mechanical energy conversion was developed.•This method quantifies the effect of vacuum pump type/size on energy consumption. This study introduces a novel approach to enhance the precision of energy estimation in Vacuum Swing Adsorption (VSA) processes. To address this, a mathematical model was developed that incorporates the vacuum pump's characteristic curve, allowing for a more realistic representation of the VSA process. The model was rigorously validated against published data from a pilot plant study, where power consumption had been directly metered. Our results demonstrate that the isentropic work of gas compression, which is commonly used to estimate the evacuation energy, underestimates energy consumption by a significant factor, approximately threefold. The root cause of this divergence is the allocation of efficiency at a moderate vacuum (e.g. 20 kPa) to the entire range of evacuation pressure (below 10 kPa). A novel electromechanical efficiency factor (hereafter ηEM) that accounts for transforming power to the required shaft work was introduced. This factor, which incorporates vacuum pump characteristics into the calculations, not only rectifies the underestimation in energy consumption but also serves as a tool to evaluate the impact of the vacuum pump type on process performance.